35. STUDY ON THE EFFECTS OF DRINKING ALKALINE MAGNESIUM IONIZED WATER ON BLOOD LIPID, BLOOD SUGAR, AND BLOOD URIC ACID INDICES ABSTRACT (Vietnam Journal of Community Medicine, 2025)
Purpose: To study the effects of drinking Magnesium alkaline ionized water on some blood lipid, blood sugar, and blood uric acid indices after two months of use.Methods: prospective study on 134 people in Quang Tri province, comparing blood lipid, blood sugar, and blood uric acid indices before and after two months of using Magnesium alkaline ionized water.Results: The average Glucose index decreased by 6.60 ± 17.87%, the group with Glucose index ≥ 5.6 mmol / l decreased by 22.62 ± 17.39 on average; the average Total Cholesterol index decreased by 13.74 ± 10.20%, the group with Total Cholesterol index > 5.2 mmol / l decreased by 27.33 ± 29.86% on average; The average triglyceride index decreased by 5.93 ± 33.55%, people with triglyceride index >1.88mmol/L decreased by 27.33 ± 29.86%; the average uric acid index decreased by 19.31 ± 1.19%, people with triglyceride >420 μmol/l, decreased by 17.22 ± 11.26%.Conclusions: After two months of using magnesium alkaline ionized water, the average blood lipid, blood sugar, and blood uric acid indices all had a clear downward trend.
Keywords: Chronic disease; alkaline ionized water; magnesium.